Pengaruh terapi pijat terhadap peningkatan Berat badan bayi - Tri Sasmi Irva; Oswati - Hasanah; Rismadefi - Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to determine the effect of massage therapy to improve baby’s weight. The design of this study was quasy experimental with pre test and post test control group approach which divided into experimental group and control group. The samples of this study were 34 babies which aged 1-3 months in Pekanbaru by using purposive sampling method. Baby massage was implemented by mothers twice a day (morning & afternoon) in experimental group in 2 weeks. The analyze used in this study were univariate and bivariate with Mann-whitney and Wilcoxon test. The result showed a significant different in babies weight between experimental and control group (p= 0,01<0,05) with 700 grams increases in baby’s weight which mean that massage therapy had effect to improve baby’s weight. This research recommended that massage therapy could be applied by mothers in daily living. Keyword: baby, massage therapy, weight gain.